2017
DOI: 10.2147/ndt.s130483
|View full text |Cite
|
Sign up to set email alerts
|

Treatment satisfaction with paliperidone extended-release tablets: open-label study in schizophrenia patients dissatisfied with previous antipsychotic medication

Abstract: ObjectiveThe aim of this study was to evaluate the changes in treatment satisfaction after switching to paliperidone extended-release (ER) in Chinese schizophrenia patients dissatisfied with their previous antipsychotic treatment.MethodsIn this 8-week, open-label, single-arm, multicenter, prospective study, 1,693 patients dissatisfied with previous antipsychotic medication were enrolled and switched to paliperidone ER tablets (3–12 mg/d) based on clinical judgment. The primary efficacy end point was change in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 27 publications
(32 reference statements)
1
4
0
Order By: Relevance
“…In our trial we found that PP1M had an overall efficacy overlapping with paliperidone ER on clinical symptoms assessed with the CGI-SCH score, psychosocial functioning, measured with the PSP score, and on subjective wellbeing under neuroleptic, assessed with the SWN-K score. This result is in accordance with previous studies on oral paliperidone (12,(25)(26)(27) and long-acting paliperidone (23,24,28,39,40). In our study we did not observe a significant decrease of cognitive symptoms neither with PP1M, nor with paliperidone ER.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In our trial we found that PP1M had an overall efficacy overlapping with paliperidone ER on clinical symptoms assessed with the CGI-SCH score, psychosocial functioning, measured with the PSP score, and on subjective wellbeing under neuroleptic, assessed with the SWN-K score. This result is in accordance with previous studies on oral paliperidone (12,(25)(26)(27) and long-acting paliperidone (23,24,28,39,40). In our study we did not observe a significant decrease of cognitive symptoms neither with PP1M, nor with paliperidone ER.…”
Section: Discussionsupporting
confidence: 94%
“…The TSQM (31) is a 14-item psychometrically robust and validated instrument comprising four domains: effectiveness (questions 1-3), side effects (questions 4-8), convenience (questions 9-11), and global satisfaction (questions [12][13][14]. The TSQM domain scores range from 0 to 100.…”
Section: Primary Outcome Measuresmentioning
confidence: 99%
See 3 more Smart Citations